2017
DOI: 10.1111/psyp.12914
|View full text |Cite
|
Sign up to set email alerts
|

Effects of prior mental effort on picture processing: An ERP investigation

Abstract: The current study examined the aftereffects of mental effort on the processing of picture stimuli using neural measures. Ninety-seven healthy young adults were randomly assigned to exercise more versus less mental effort on a writing task. Then participants viewed positive, negative, and neutral affective images while P1, N1, P2, N2, P3, and late positive potential (LPP) magnitudes to the images were assessed. We found that performing the more (versus less) effortful writing task caused more negative N2 amplit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 57 publications
(140 reference statements)
1
13
0
Order By: Relevance
“…An initial meta-analysis of the after-effects of exercising selfcontrol found evidence for consistent, large effects (Hagger, Wood, Stiff, & Chatzisarantis, 2010), but more recent meta-analyses concluded that the effect does not differ from zero after adjusting for publication bias (Carter, Kofler, Forster, & Mccullough, 2015;Carter & McCullough, 2014). However, the validity of the bias correction techniques used by Carter and McCullough have been called into question (see Inzlicht, Gervais, & Berkman, 2015b;Moreno et al, 2009;Reed, 2015;Simonsohn, 2017), and although one multi-laboratory test of the resource model found a non-significant after-effect of self-control exertion (Hagger et al, 2016), other preregistered, large-sample studies have found statistically significant (if smaller than expected) effects (Dang, Liu, Liu, & Mao, 2017;Garrison, Finley, & Schmeichel, 2017). Schmeichel, & Macrae, 2014), exercising self-control is an aversive activity that causes shifts in motivation and attention that combine to undermine subsequent attempts at self-control.…”
Section: Theoretical Accounts Of Self-controlmentioning
confidence: 99%
See 1 more Smart Citation
“…An initial meta-analysis of the after-effects of exercising selfcontrol found evidence for consistent, large effects (Hagger, Wood, Stiff, & Chatzisarantis, 2010), but more recent meta-analyses concluded that the effect does not differ from zero after adjusting for publication bias (Carter, Kofler, Forster, & Mccullough, 2015;Carter & McCullough, 2014). However, the validity of the bias correction techniques used by Carter and McCullough have been called into question (see Inzlicht, Gervais, & Berkman, 2015b;Moreno et al, 2009;Reed, 2015;Simonsohn, 2017), and although one multi-laboratory test of the resource model found a non-significant after-effect of self-control exertion (Hagger et al, 2016), other preregistered, large-sample studies have found statistically significant (if smaller than expected) effects (Dang, Liu, Liu, & Mao, 2017;Garrison, Finley, & Schmeichel, 2017). Schmeichel, & Macrae, 2014), exercising self-control is an aversive activity that causes shifts in motivation and attention that combine to undermine subsequent attempts at self-control.…”
Section: Theoretical Accounts Of Self-controlmentioning
confidence: 99%
“…For example, after suppressing their emotions, participants have been found to show a reduced error-related negativity (ERN), a neurophysiological index of conflict monitoring (Inzlicht & Gutsell, 2007;Wang, Yang, & Wang, 2014). Additionally, after exerting self-control, participants have been found to exhibit reduced attentional engagement with visual stimuli as measured by ERPs during a passive image-viewing task (Garrison, Crowell, Finley, & Schmeichel, 2017). Below, we review studies specifically examining reward-related after-effects of self-control; these have focused primarily on the feedback-related negativity (FRN) and alpha asymmetry.…”
Section: Electrophysiological Evidencementioning
confidence: 99%
“…The process model, by contrast, predicts that exercising self-control may influence subsequent motivation and attention even when self-control is not required. Consistent with this view, the aftereffects of self-control have been observed among individuals who simply view emotional pictures without attempting to control their responding (e.g., Finley & Schmeichel, 2018;Garrison, Crowell, Finley, & Schmeichel, 2017;Schmeichel, Crowell, & Harmon-Jones, 2016; see also Crowell, Kelley, & Schmeichel, 2014;Schmeichel, Harmon-Jones, & Harmon-Jones, 2010).…”
Section: The Process Model Of Ego Depletionmentioning
confidence: 86%
“…For example, after suppressing their emotions, participants have been found to show a reduced error related negativity (ERN), a neurophysiological index of conflict monitoring (Inzlicht & Gutsell, 2007;Wang, Yang, & Wang, 2014). Additionally, after exerting self-control participants have been found to exhibit reduced attentional engagement with visual stimuli as measured by ERPs during a passive image viewing task (Garrison, Crowell, Finley, & Schmeichel, 2017). Below, we review studies specifically examining reward-related aftereffects of self-control; these have focused primarily on the feedback related negativity (FRN) and alpha asymmetry.…”
Section: Electrophysiological Evidencementioning
confidence: 99%